Fruit and vegetable consumption and its determinants amongst Moroccan women, in the context of nutrition transition - Landais, Edwige (2012)
Purpose: Morocco is undergoing a nutrition transition, characterised by increasing prevalence non-communicable diseases (NCD), including obesity. In that context, it is crucial to focus on fruit and vegetable (F&V) intake as they may have a preventive effect on weight gain and NCDs. Objectives: The objectives of the present work were: to develop an objective measure of F&V intake and to provide a holistic understanding of factors that may influence F&V consumption, such as socio-demographic and psychosocial factors. Methods: The target population was Moroccan women (20-49 years), living in the urban area of Rabat-Salé. This PhD involved three different studies: the first was based on focus groups that yielded qualitative data of women’s views of F&V; the second study involved validating a quantitative F&V Food Frequency Questionnaire (FFQ); the third a cross sectional population survey-which incorporated findings from studies 1 and 2 to assess dietary intake and the factors influencing F&V consumption. Results: Validation analyses suggested that the quantitative FFQ developed was reliable and valid to measure F&V intake. The mean F&V intake was 213g per day. Women with higher education, higher economic status and better knowledge scores ate significantly larger amounts of F&V than others. Processed food consumption was inversely associated with vegetable intakes. In terms of psychosocial factors, the strongest predictor of intention to eat fruit was control beliefs. Normative beliefs were the strongest predictor of intention to eat vegetables. Intention was the strongest predictor of both fruit and vegetable consumption. Conclusion: The data collected gave an overview of the amount of fruit and vegetables consumed by urban Moroccan women, and enabled a better understanding of the determinants of fruit and vegetable intake. As a consequence, data sheds light on possible avenues for policies and nutrition interventions to focus on in Morocco, in order to increase fruit and vegetable consumption.